Espionage in the ancient world : an annotated bibliography of books and articles in Western languages - Sheldon, R. M., 1948- (McFarland & Co., 2003)
""Splendid ... excellent indexes ... a wealth of information ... recommended""--Booklist; ""well researched, organized and indexed ... an excellent work ... highly recommended""--Choice; ""very valuable""--The NYMAS Review; ""delightful ... impressive ... highly informative""--Reference & User Services Quarterly; ""essential""--CIA Website; ""very valuable""--www.strategypage.com; ""immensely useful""--Military History; ""comprehensive ... worthwhile""--Cryptologia. Here, for the first time, is a comprehensive guide to the literature of ancient intelligence. The entries present books and periodical article